Effect of Genetic Variation in CYP450 on Gonadal Impairment in a European Cohort of Female Childhood Cancer Survivors, Based on a Candidate Gene Approach: Results from the PanCareLIFE Study - van der Perk, M E Madeleine; Broer, Linda; Yasui, Yutaka; Robison, Leslie L; Hudson, Melissa M; Laven, Joop S E; van der Pal, Helena J; Tissing, Wim J E; Versluys, Birgitta; Bresters, Dorine; Kaspers, Gertjan J L; de Vries, Andrica C H; et al. (Cancers, 2021)
BACKGROUND: Female childhood cancer survivors (CCSs) carry a risk of therapy-related gonadal dysfunction. Alkylating agents (AA) are well-established risk factors, yet inter-individual variability in ovarian function is observed. Polymorphisms in CYP450 enzymes may explain this variability in AA-induced ovarian damage. We aimed to evaluate associations between previously identified genetic polymorphisms in CYP450 enzymes and AA-related ovarian function among adult CCSs. METHODS: Anti-Müllerian hormone (AMH) levels served as a proxy for ovarian function in a discovery cohort of adult female CCSs, from the pan-European PanCareLIFE cohort (n = 743; age (years): median 25.8, interquartile range (IQR) 22.1-30.6). Using two additive genetic models in linear and logistic regression, nine genetic variants in three CYP450 enzymes were analyzed in relation to cyclophosphamide equivalent dose (CED) score and their impact on AMH levels. The main model evaluated the effect of the variant on AMH and the interaction model evaluated the modifying effect of the variant on the impact of CED score on log-transformed AMH levels. Results were validated, and meta-analysis performed, using the USA-based St. Jude Lifetime Cohort (n = 391; age (years): median 31.3, IQR 26.6-37.4). RESULTS: CYP3A4*3 was significantly associated with AMH levels in the discovery and replication cohort. Meta-analysis revealed a significant main deleterious effect (Beta (95% CI): -0.706 (-1.11--0.298), p-value = 7 × 10-4) of CYP3A4*3 (rs4986910) on log-transformed AMH levels. CYP2B6*2 (rs8192709) showed a significant protective interaction effect (Beta (95% CI): 0.527 (0.126-0.928), p-value = 0.01) on log-transformed AMH levels in CCSs receiving more than 8000 mg/m2 CED. CONCLUSIONS: Female CCSs CYP3A4*3 carriers had significantly lower AMH levels, and CYP2B6*2 may have a protective effect on AMH levels. Identification of risk-contributing variants may improve individualized counselling regarding the treatment-related risk of infertility and fertility preservation options.
Keywords: candidate gene approach; childhood cancer survivors; cytochrome P450 genes; anti-Müllerian hormone; ovarian function; chemotherapy